STERILIZATION EFFICACY AND DESINFECTION OF CAGES TO REDUCE BACTERIAL INFECTIONS - Gelgel, Ketut Tono Pasek; Sudipa, Putu Henrywaesa (Buletin Veteriner Udayana, 2020)
Biosecurity efforts on chicken farms such as using antiseptics need to be modified so that the aim of suppressing the bacteria in the cage is effective. The purpose of this research is to find alternative methods for sterilization and disinfection of broiler cages and to find out the number and type of bacterial contamination in broiler cages. In this study two cages were used, the first cage washed with detergent and given Povidon Iodine disinfectant. In the second cage after washing with detergent, the floor of the cage is burned/heated and the cage wall is disinfected. Then the blood agar media is placed on the cage’s floor and opened for 1 hour. Then the blood agar media examined in the laboratory to see the number and type of bacteria that grow. All samples were tested with T-Test. The results showed that disinfection with disinfectants had more number of colonies (206 colonies, with an average of 29.85 colonies) than cages that used a heating method with a stove (182 colonies, with an average of 26 colonies). The results show there is no significant difference between sterilization treatment and disinfection treatment. The method of sterile sterilization by heating using a stove is slightly more effective than disinfection by using disinfectants seen from the number of bacterial colonies that grow, although the difference between the two methods is very little.